The power of collaboration: using internet-based tools to facilitate networking and benchmarking within a consortium of academic health centers. - Korner EJ; Oinonen MJ; Browne RC (Journal of Medical Systems, 2003)
The University HealthSystem Consortium (UHC) represents a strategic alliance of 169 academic health centers and associated institutions engaged in knowledge sharing and idea-generation. The use of the Internet as a tool in the delivery of UHC's products and services has increased dramatically over the past year and will continue to increase during the foreseeable future. This paper examines the current state of UHC-member institution driven tools and services that utilize the Web as a fundamental component in their delivery. The evolution of knowledge management at UHC, its management information and reporting tools, and expansion of e-commerce provide real world examples of Internet use in health care delivery and management. Health care workers are using these Web-based tools to help manage rising costs and optimize patient outcomes. Policy, technical, and organizational issues must be resolved to facilitate rapid adoption of Internet applications.